Selective Competence Renewal and Organizational Performance in the Nigerian Telecommunication Sector - Akpotu, Christopher; Ginah, Ginah O. (Advances in Social Sciences Research Journal, 2015)
This study primarily is a scientific in-road into deeper understanding of the strategic implication of selective competence renewal influence on organizational performance in the telecommunication sector of Nigeria. This attempt underscores the role of employee competencies and skills in the characteristic competitive business environment. The study has used the questionnaire primarily as the instrument for obtaining data having confirmed its validity and reliability with a cronbach alpha value of 0.81. The data were analyzed inferentially and it was shown that selective competence renewal is a strategic competitive component of organizational politics at the macro level that ensures agility, improved service delivery and innovative practices. It was concluded based on the findings that selective competence renewal encourages and strengthen firms from competitiveness. It has also been recommended based on the findings that organization should promote skill/competencies enhancement programmes that are targeted at value adding and encourage knowledge sharing among work members.